2011
DOI: 10.1016/j.nlm.2010.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of mecamylamine-sensitive mushroom body neurons in insect olfactory learning

Abstract: In insects, cholinergic neurons are thought to transmit olfactory conditioned stimulus (CS) to the sites for associating the CS with unconditioned stimulus (US), but the types of acetylcholine (ACh) receptor used by neurons participating in the association have not been (250 words).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 59 publications
1
24
0
Order By: Relevance
“…It has been shown that local uncaging of cGMP (but not NO) in the antennal lobe facilitates LTM formation in honey bees [20]. In cockroaches, we obtained evidence suggesting that the mushroom body is the site where olfactory CS and sucrose US converge for salivary conditioning [30]. The mushroom body of 9 cockroaches is a highly organized neuropil, in which the intrinsic neurons (Kenyon cells) are organized into discrete structural subunits [16,17].…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…It has been shown that local uncaging of cGMP (but not NO) in the antennal lobe facilitates LTM formation in honey bees [20]. In cockroaches, we obtained evidence suggesting that the mushroom body is the site where olfactory CS and sucrose US converge for salivary conditioning [30]. The mushroom body of 9 cockroaches is a highly organized neuropil, in which the intrinsic neurons (Kenyon cells) are organized into discrete structural subunits [16,17].…”
Section: Discussionmentioning
confidence: 77%
“…Salivary neurons exhibit spontaneous spike activities [10,[27][28][29][30]. Responses of salivary neurons to peppermint or vanilla odor (R) were measured as relative increase of the spike frequency from the spontaneous level, i.e., (Rs-Ro)/Ro, where Rs or Ro is the summed spike frequency of two salivary neurons during a 2-s period of odor stimulation or that during a 2-s period before the onset of odor stimulation, respectively [10].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations